2019
DOI: 10.3390/cancers11010100
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Generation and Cancer: Contributors and Consequences

Abstract: The high occurrence of cancer-associated thrombosis is associated with elevated thrombin generation. Tumour cells increase the potential for thrombin generation both directly, through the expression and release of procoagulant factors, and indirectly, through signals that activate other cell types (including platelets, leukocytes and erythrocytes). Furthermore, cancer treatments can worsen these effects. Coagulation factors, including tissue factor, and inhibitors of coagulation are altered and extracellular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 175 publications
2
80
0
2
Order By: Relevance
“…Using C5-producing tumor cell lines, it was shown that C5a can be generated by a still not identified cell membrane-bound serine protease 14 . Thrombin is produced in tumors and has potent pro-tumoral activity 25 . Therefore, it is tempting to speculate that the cleavage of C5 will be yet another mechanism of its pro-tumoral activity in situ.…”
Section: Canonical Mechanisms Of Initiationmentioning
confidence: 99%
“…Using C5-producing tumor cell lines, it was shown that C5a can be generated by a still not identified cell membrane-bound serine protease 14 . Thrombin is produced in tumors and has potent pro-tumoral activity 25 . Therefore, it is tempting to speculate that the cleavage of C5 will be yet another mechanism of its pro-tumoral activity in situ.…”
Section: Canonical Mechanisms Of Initiationmentioning
confidence: 99%
“…The plasticity of tumor cells permits them to adopt a range of migratory modes, of which the amoeboid phenotype is defined by plasma membrane blebbing, and is implicated in tumor metastasis 1 . The tumor environment is thrombotic (reviewed in 13 ), in part due to the low integrity of tumor vessels, and thrombin has been proposed to increase the invasiveness of MDA-MB-231 breast cancer cells 38 . Here we identify thrombin as a potent stimulus for blebbing in breast cancer cells, and establish that activation of its receptor PAR2 is sufficient to induce this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor vessels are notoriously leaky and the tumor environment has been described as being in a pathological state of coagulation, which may be exacerbated by certain chemotherapies 11 . Consequently, cancer cells may exist within, and contribute to, a milieu enriched in various components of the coagulation cascade, including thrombin 12 (reviewed in 13 ). Thrombin acts on the G protein-coupled protease activated receptors (PARs) 1-4 [14][15][16][17][18] to irreversibly sever a part of their N-terminal extracellular domain exposing a tethered ligand, which activates the receptor through an intramolecular interaction.…”
Section: Introductionmentioning
confidence: 99%
“…We also specifically looked at the clotting global tests as their availability in clinical settings is widely known [11,[25][26][27]. Mean PT was statistically longer in the high tPA group but didn't exceed the upper reference value at the onset and after 3 and 6 cycles of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%